Incidence of hippocampal and perihippocampal brain metastases and impact on hippocampal-avoiding radiotherapy: a systematic review and meta-analysis - Wiegreffe, Shari; Sarria, Gustavo Renato; Layer, Julian; Dejonckheere, Egon; Nour, Younèss; Schmeel, Carsten; Giordano, Frank Anton; Schmeel, Christopher; Popp, Ilinca; Grosu, Anca-Ligia; Gkika, Eleni; Stefaan Dejonckheere, Cas (Radiotherapy and oncology, 2024)
Background and Purpose - In patients requiring prophylactic cranial irradiation (PCI) or whole-brain radiotherapy (WBRT) for brain metastases (BMs), hippocampal avoidance (HA) has been shown to preserve neurocognitive function and quality of life. Here, we aim to estimate the incidence of hippocampal and perihippocampal BMs and the subsequent risk of local undertreatment in patients undergoing hippocampal sparing radiotherapy. - Materials and Methods - MEDLINE, Embase, and Scopus were searched with the terms “Hippocampus”, “Brain Neoplasms”, and related terms. Trials reporting on the incidence of hippocampal and/or perihippocampal BMs or hippocampal failure rate after PCI or WBRT were included. - Results - Forty records were included, encompassing a total of 5,374 patients with over 32,570 BMs. Most trials employed a 5 mm margin to define the HA zone. In trials reporting on BM incidence, 4.4 % (range 0 − 27 %) and 9.2 % (3 − 41 %) of patients had hippocampal and perihippocampal BMs, respectively. The most common risk factor for hippocampal BMs was the total number of BMs. The reported failure rate within the HA zone after HA-PCI or HA-WBRT was 4.5 % (0 − 13 %), salvageable with radiosurgery in most cases. SCLC histology was not associated with a higher risk of hippocampal failure (OR = 2.49; p = 0.23). In trials comparing with a conventional (non-HA) PCI or WBRT group, HA did not increase the hippocampal failure rate (OR = 1.90; p = 0.17). - Conclusion - The overall incidence of hippocampal and perihippocampal BMs is considerably low, with a subsequent low risk of local undertreatment following HA-PCI or HA-WBRT. In patients without involvement, the hippocampus should be spared to preserve neurocognitive function and quality of life.